ANALISIS PRODUKTIVITAS KERJA DI PT. TASPEN (PERSERO) KANTOR CABANG UTAMA SEMARANG - Nico Handani; Diah Hariani; Aufarul Marom (Journal of Public Policy and Management Review, 2013)
A workload that increasing within company is complex problem, especially there on the job service. Company productivity of work describe an overview of the performance of a state how the company manages the resources.The Purpose of this research is to found how the productivity of work on PT. TASPEN (persero) Main Branch Office Semarang as seen from the quantity of work, quality of work and the factors that affect productivity of work.Research method used is descriptive qualitative type, and data used was primary data an obtained from interviews with informants from Kabid Persum PT. TASPEN (persero) Main Branch Office Semarang then Kasie Personalia PT. TASPEN (persero) Main Branch Office Semarang, and secondary data was obtained from literature study, archival sources, personal dan official documents. Techniques collecting data an obtained from interviews, observation, literature study and documentation. Which of data an obtained then analyzed and interpreted to explain the data collected.Research result showed that productivity of work on PT. TASPEN (persero) Main Branch Office Semarang is pretty good with productivity factors are sufficient to support the sustainability of the company, where each month is always increase the participants who submitted claim in PT. TASPEN (persero) Main Branch Office Semarang.